(untitled) (Contemporary Journal of Social Science Review, 2023)
Retail organizations operating in the U.S. face mounting demands from regulations and customers who seek sustainable practices, prompting a clear transformation in their business responses to both challenges. Circular economy strategies are gaining traction as an essential element for achieving these objectives, yet the direct linkage between sustainability efforts and financial success remains nuanced. The study at hand embarks on a methodical exploration of the symbiotic relationship between circular economy adoption, sustainable operations management, and competitive edge within the retail sector, eschewing the traditional perception of sustainability as merely a financial burden. The narrative of ’green’ transformation is reframed as an opportunity for retailers to distinguish themselves in a fiercely competitive market. The circular model, characterized by its restorative and regenerative approach, posits resource efficiency not as an ethical choice but as a catalyst for innovative growth and profitability. The research advances this discussion by dissecting how sustainability investments, when woven into the fabric of operations ranging from supply chain and product management to store operations and waste management can drive a plethora of positive business outcomes. This includes elevating brand loyalty, mitigating risks, reducing costs, and ultimately, opening new revenue streams. Leveraging a robust mix of qualitative and quantitative methodologies, including an analysis of corporate sustainability narratives, financial performance, and consumer sentiment, this study elucidates the operational levers that convert sustainability efforts into bottom-line benefits. The culmination of this research is a comprehensive guide for retail executives, offering a blueprint for the implementation of a Sustainable Operations Strategy that not only aligns with but champions the principles of circularity and regeneration, thus ensuring the longevity and profitability of their businesses in an era of increasing ecological and social consciousness.